Effect of the plantation of Pennisetum purpureum cv. Cuba CT-115 on the variation of the physico-chemical properties of the soils in the Picadura farm, Cuba - Crespo, Gustavo; Otero, L?zara (Cuban Journal of Agricultural Science, 2011)
It was studied the effect of the plantation of the P. purpureum cv. CUBA CT-15 pasture by the plowing method and perpendicular to the slope, in the physico-chemical properties of the brown calcic carbonated lithic and brown calcic carbonated soils, in the unit 123 of the Picadura farm, in the Mayabeque province, Cuba. The properties analyzed were: texture (T), humidity (H), apparent density (AD), changeable cations (CC), and bases interchange capacity (BIC) at different depths. The results were determined the central trend statistics: mean, standard deviation, and coefficient of variation. Student?s t-test was used for the comparison of the means. In the brown calcic carbonated lithic soil, after the pasture was planted, the AD decreased from 1.2 to 0.90 g/m3 at both depths, whereas the clay content was superior to 60 %. In this soil, the BIC and the Ca2+ increased, and the Mg2+ tended to decline. In the brown calcic carbonated soil, the predominant texture was also clayish (63 to 75 % of clay) and there was significant increase of the Ca2+ and of the BIC, without variation in the rest of the cations. It was concluded that the plantation of this pasture species perpendicular to the slope decreases the AD, and increases the movement of cations through the profile of both types of soils. This is a sign of improvement of the permeability, provoking higher resistance to erosion. Key words: P. purpureum cv. Cuba CT-115, plantation, soil properties, cattle area, Cuba.